Common Misconceptions Regarding Pediatric Auditory Processing Disorder - Iliadou, Vasiliki; Kiese-Himmel, Christiane (Frontiers in Neurology, 2018)
Pediatric hearing evaluation based on pure tone audiometry does not adequately reflect how a child hears in everyday life. This practice is particularly inadequate when evaluating the difficulties children experiencing Auditory Processing Disorder (APD) have in school or on the playground. Despite the marked increase in research on pediatric APD, there remains limited access to proper evaluation worldwide. This perspective article presents five common misconceptions of APD that contribute to inappropriate or limited management in children experiencing these deficits. The misconceptions discussed are: 1) the disorder cannot be diagnosed due to the lack of a gold standard diagnostic test; 2) making generalizations based on profiles of children suspected of APD and not diagnosed with the disorder; 3) it is best to discard an APD diagnosis when another disorder is present; 4) arguing that the known link between auditory perception and higher cognition function precludes the validity of APD as a clinical entity; and 5) APD is not a clinical entity. These five misconceptions are presented, described and rebutted using published data as well as critical thinking on current available knowledge on APD.